The serological survey on bluetongue virus infection in sheep - Feridun ÖZTÜRK; Sibel YAVRU; Saffet ERÖZ (Eurasian Journal of Veterinary Sciences)
A swn of 86 blood sera of sheep were collected from Konya Livestock Research Centre. The blood sera were examined to detennine the presence of neutralizing antibodies to BTV (Bluetongue Virus), type SA4 by microneutralization test. BHK (Baby Hamster Kidney) permanent eeliline was used for production and titration of BTV and neutralisation test. Glascow Eagle's MEM (Minimum Essential Medium) with 10 % calf sera for cell medium and Glascow Eagle's MEM without sera for virus medium were used in this research. The blood sera were tested at the rate of 1/10 dilution. At the end of the microneutralization test, the 31 (36.04 %) sheep blood were found seropozitive to BTV, type SA4.